Microbial diversity in terrestrial Antarctic biotopes - Romanovskaya, V. A.; Tashyrev, O. B.; Rokitko, P. V.; Shilin, S.O.; Chernaya, N. A.; Tashyreva, A.O. (Ukrainian Antarctic Journal, 2009)
It is established, that the total number of chemoorganotrophic aerobic microorganisms in a soil, sludge of reservoirs, on a grass, mosses and lichens on islands Galindez, Skua, Corner, Barchans, Irizar, Uruguay, Jalour, Petermann, Berthelot, Cruls, Three little pigs, King-George made 105 -108 cells/g of a sample that is less on 2-3 order, than in regions with a temperate climate. From samples of moss, lichen, grass, soil are isolated methylotrophic bacteria (102-104 cells/g of a sample). It is shown, that in the Antarctic lichens frequency of an occurence of coal-black yeast and also their total number is significantly higher (102-104 cells/g of sample), than in other Antarctic biotopes. Coal-black pigments are extracted from Antarctic yeast Exophiala nigra. These pigments are identical to melanin according to results of studying of specific chemical tests, UV spectra and other properties. For the first time presence on vertical rocks in Antarctic Region of bacteria and yeast, resistant to high dozes UV radiations is shown. The lethal doze of UV radiation for Antarctic pink pigmented strains Methylobacterium exceeded 200–250 J/m2, for coal-black yeast – 500–800 J/m2, for red-pigmented yeast –1200–1500 J/m2. In whole, in the Antarctic Region representatives of several phylogenetic lines are found: Proteobacteria, Firmicutes, Actinobacteria, and also yeast. Obtained results indicate to a taxonomic diversity of microorganisms in terrestrial biotopes of Antarctic Region.